AKTIVITAS ANTIOKSIDAN EKSTRAK DAUN JOMBANG (Taraxacum officinale F.H. Wigg) PADA LOKASI BERBEDA MENGGUNAKAN METODE DPPH DAN FRAP - Ayu Nawangsih (2023)
Jombang plant (Taraxacum officinale F.H Wigg) or known as dandelions is a medicinal plant which is rich in various nutrients and biologically active substances, and its polyphenolic compounds are considered to be responsible for the biological activity in antioxidant, anti-inflammatory and antitumor effects. This study aims to determine the antioxidant activity of jombang plants taken from the Tawangmangu and Batu locations. The antioxidant test was carried out using the DPPH (2,2-Diphenyl-1-Pikrihidrazi) and FRAP (Ferric Reducing Antioxidant Power) methods. The results of increasing the total phenolic content were 29.62 ± 0.53 in the 50% ethanol extract of Tawangmangu and 21.57 ± 0.69 in the 50% ethanol extract of Batu, respectively. The total levels of flavonoids in the 50% ethanol extract of Tawangmangu and Batu obtained results of 16.24 ± 0.93 and 8.06 ± 0.36, respectively. The highest antioxidant activity was obtained from jombang leaf extract obtained from Tawangmangu with an IC50 value of 73,36 ± 1.65 ppm in the DPPH method and 34.57 ± 0.07 ppm in the FRAP. The percentage inhibition of the two extracts did not show a significant difference between the DPPH and FRAP methods (p>0.05).